2008
DOI: 10.1007/s11829-008-9045-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 and O3 on leaf damage and insect abundance in a soybean agroecosystem

Abstract: By altering myriad aspects of leaf chemistry, increasing concentrations of CO 2 and O 3 in the atmosphere derived from human activities may fundamentally alter the relationships between insect herbivores and plants. Because exposure to elevated CO 2 can alter the nutritional value of leaves, some herbivores may increase consumption rates to compensate. The effects of O 3 on leaf nutritional quality are less clear; however, increased senescence may also reduce leaf quality for insect herbivores. Additionally, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 83 publications
1
50
0
Order By: Relevance
“…Arthropod family richness was not affected by treatments, but the authors observed shifts in arthropod community composition over a four-year period. Results like the ones listed here and others (e.g., Holton et al 2003, Dermody et al 2008 show that insect communities in the 21 st century will be different from current ones due to elevated CO 2 , elevated …”
supporting
confidence: 80%
“…Arthropod family richness was not affected by treatments, but the authors observed shifts in arthropod community composition over a four-year period. Results like the ones listed here and others (e.g., Holton et al 2003, Dermody et al 2008 show that insect communities in the 21 st century will be different from current ones due to elevated CO 2 , elevated …”
supporting
confidence: 80%
“…Growth under elevated CO 2 increases leaf carbohydrates and reduces the concentration of defensive CystPI activity, which together greatly increase the suitability of foliage for beetles. Leaf damage and the number of Japanese beetles, as well as numbers of other folivorous insects, are greater in plots exposed to elevated compared with ambient CO 2 (Hamilton et al, 2005;Dermody et al, 2008). Photo credit: B. O'Neill.…”
Section: Hormones and Global Change: Putative Mechanismsmentioning
confidence: 99%
“…Most of the quantitative assessments are monodisciplinary and therefore disregard any mechanisms that affect agricultural productivity other than direct climate change effects. There are some qualitative studies that discuss the potentially severe impacts of indirect climate change effects such as cropland inundation, erosion, and salinization caused by sea level rise (31), altered crop resistance to insect damage (32), and the response of pests and pathogens to climate change (33).…”
mentioning
confidence: 99%